Penguatan Reformasi Birokrasi Di Indonesia Menuju Era Society 5.0 - Wulandari, Sri (LPPM Universitas Bina Sarana Informatika, 2023)
This study provides valuable insight regarding (KemenPANRB) efforts to accelerate towards the Society 5.0 era in Indonesia. Using qualitative methods and applying a cluster analysis approach with NVivo12 Plus software, this research highlights the implementation of the merit system as part of planning governance in the Ministry of Administrative and Bureaucratic Reform. The employee appointment, promotion and promotion process involves a comprehensive examination of competency and expertise, taking into account integrity and morality. However, research findings also reveal that there are significant obstacles in efforts to encourage bureaucratic reform. Although KemenPANRB has tried to ensure integrity and competence in the administrative process. The success of moving towards the Society 5.0 era, where public services must be driven by technology and information, is questioned by this obstacle. Therefore, further steps are needed to overcome these obstacles, such as changing organizational culture, providing technological training to bureaucratic personnel, and strengthening the supervisory system to overcome bureaucratic pathology and corruption. Thus, this study highlights the real challenges that must be faced in achieving comprehensive bureaucratic reform in Indonesia.